Design and development of ocean monitoring system based on GPS - Mohd Salleh, Anuar (2017)
Coastal zone of Malaysia has a vital role in socio-economic and environmental in pursuing the country development. However, it constantly faces a threat from coastal erosion. The report year 2013 from the Department of Irrigation and Drainage Malaysia showed 29% of Malaysian coastal has been experiencing erosion at various levels and primarily driven by ocean waves. Hence, this study focused on developing the ocean monitoring system consists of a buoy with Global Positioning System (GPS) technology, reference station and data analysis techniques. The buoy was developed by considering local factors and improves the performance of existing buoy. Comparison with existing GPS buoy has found that the GPS buoy is far exceeded in term of physical specifications, costs, sensors sensitivity and observation interval. Based on the verification with slider machine, this system has been able to provide high accuracy result less than 0.5 cm compared to the standard value of slider machine. The RMS error from data analysis technique is less than 0.0016 m. Validation with Department of Survey and Mapping Malaysia (JUPEM) automatic tide gauges have found both methods agreed on tidal pattern with small discrepancy of less than 10 cm. Encouraging results were also obtained when the observations off coast Senggarang compared with manual observations, historical data and Malaysia Meteorological Department (MetMalaysia) wave forecasting. This system has been observing the same tidal patterns with data analysis RMS error less than 0.0013 m. Comparison with the height of historical wave data and wave forecast shows the results of observations of this system are in the range of comparisons made. Difference of 20 mm was obtained when compared with the wave height observed manually. The usefulness of GPS buoy data also has been demonstrated in analyzing the monsoon wind influences at off coast Senggarang.